Understanding Culture through Animation: From the World to Malaysia - Mat Omar, Mohd Amir; Ahmad Ishak, Md Sidin (Jurnal Pengajian Media Malaysia, 2011)
Generally, culture is aimed to be preserved the way they are thus maintaining the status quo of their origins. The growth and increased range of available local and foreign media content have raised numerous questions as to the impact and effects it brings towards culture. As a mature international industry and a rapidly growing local one, animations films have taken a role in introducing the cultural characteristics of various nations and backgrounds. Similar with other products of different geographical sources, animation carries a reflection of their respective cultural backgrounds. This paper attempts to understand the links between culture and animation, how animation has taken place, how animation have been studied and how animation have been described.